2012
DOI: 10.1007/s10802-011-9607-2
|View full text |Cite
|
Sign up to set email alerts
|

Objectively-Measured Impulsivity and Attention-Deficit/Hyperactivity Disorder (ADHD): Testing Competing Predictions from the Working Memory and Behavioral Inhibition Models of ADHD

Abstract: Impulsivity is a hallmark of two of the three DSM-IV ADHD subtypes and is associated with myriad adverse outcomes. Limited research, however, is available concerning the mechanisms and processes that contribute to impulsive responding by children with ADHD. The current study tested predictions from two competing models of ADHD-working memory (WM) and behavioral inhibition (BI)-to examine the extent to which ADHD-related impulsive responding was attributable to model-specific mechanisms and processes. Children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
89
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 80 publications
11
89
1
3
Order By: Relevance
“…Further, it supports the assumption that WM is crucial for the mental activities basic to children's intelligence [59], and is consistent with the idea that neuropsychological impairments (e.g., in WM) are responsible for the lower level of intellectual performance typically found in children with ADHD [1]. 11 …”
Section: Memory and Motivationsupporting
confidence: 83%
“…Further, it supports the assumption that WM is crucial for the mental activities basic to children's intelligence [59], and is consistent with the idea that neuropsychological impairments (e.g., in WM) are responsible for the lower level of intellectual performance typically found in children with ADHD [1]. 11 …”
Section: Memory and Motivationsupporting
confidence: 83%
“…Therefore, it seems that the presence of OSA causes alterations in latency, prolonging it, with a cascade effect on brain areas used for abstraction, including the frontal (Fz), central (Cz) and parietal (Pz). The same was observed by Huang et al 20 Another possible explanation is related to the fact that attention disorder can also cause abnormalities in working memory, which uses attention to follow its function 21,22 . A study focusing on an analysis of working memory related to attention could better define the relationship between attention deficit and sleep disorders, and changes in working memory due to altered latencies.…”
Section: Latencysupporting
confidence: 59%
“…This can be associated with cognitive deficits other than those described above and changes in IQ 26 . The functional impairment of the frontal cortex can cause low performance of superior mental executive functions and lack of behavioural inhibition, which are essential for the development of other mental functions such as verbal and nonverbal memory, self-regulation of affect and motivation 22 . Imaging studies are other sources of evidence that suggest the possibility of neuronal damage in patients with apnea and hypoxemia, as was observed in our study.…”
Section: Osa and P300mentioning
confidence: 99%
“…Moreover, these findings build on a growing body of research that suggests WM impairments underlie DSM-5-defined core ADHD-related hyperactivity (Alderson, Rapport, Kasper, Sarver, & Kofler 2012;Rapport et al, 2009), rapid-response impulsivity (Raiker et al, 2012), inattention (Kofler, Rapport, Bolden, Sarver, & Raiker, 2010), and disinhibition (Alderson et al, 2010), as well as secondary symptoms commonly associated with the disorder, such as social deficits (Kofler et al, 2011) and academic difficulties (Rennie, Beebe-Frankenberger, & Swanson, 2014). Alternative models, (Sonuga-Barke, 2003;Halperin & Schulz, 2006) have suggested that identification of a single-core neurocognitive deficit of ADHD is overly simplistic and point to the high degree of within-and between-study variability in neurocognitive task performance by affected children.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, the correlational nature of previous studies preclude interpretations about the directional relationship between the choice-impulsivity and WM constructs. That is, although findings from recent mediation-model studies suggest that ADHD-related WM impairments are upstream of behavioral inhibition deficits (Alderson, Rapport, Hudec, Sarver, & Kofler, 2010) and rapid-response impulsivity (Raiker, Rapport, Kofler, & Sarver, 2012), no studies to date have examined the directional relationship between WM and choiceimpulsivity in children diagnosed with ADHD. Findings that explicate the directional relationship between WM and choice-impulsivity are expected to have strong heuristic (e.g., informing model development and refinement) and applied (e.g., clarify appropriate targets for ADHD treatments) implications.…”
mentioning
confidence: 99%